Two pairs of chiral lanthanide–oxo clusters Ln14 induced by amino acid derivatives. Issue 39 (16th September 2021) - Lu, Tian-Qi; Yin, Jia-Jia; Chen, Cheng; Shi, Hai-Yan; Zheng, Jun; Liu, Zhengjie; Fang, Xiaolong; Zheng, Xiu-Ying
Abstract : Two pairs of chiral lanthanide–oxo clusters l -/d -Ln 14 (Ln = Y/Dy) have been obtained under the action of anion template. The solid-state circular dichroism (CD) spectra of l -Y 14 /d -Y 14 and l -Dy 14 /d -Dy 14 displayed mirror symmetry effects. Abstract : Two pairs of pure enantiomers of high-nuclearity chiral lanthanide–oxo clusters with the formulas [Y14 (L)16 ( μ 3 -OH)16 (H2 O)20 ]·(ClO4 )10 · x H2 O ( x ≈ 55; L = l -L − for l -Y 14 ; L = d -L − for d -Y 14 ) and [Dy14 (L)16 ( μ 3 -OH)16 (H2 O)20 ]·(ClO4 )10 · x H2 O ( x ≈ 67; L = l -L − for l -Dy 14 ; L = d -L − for d -Dy 14 ) were prepared in the presence of chiral ligands N -acetyl-l -alanine (l -HL) and N -acetyl-d -alanine (d -HL). Structural analysis showed that four cubane-like units as building blocks sharing vertices formed the lanthanide–oxo cluster unit (ClO4 )2 @[Y12 ( μ 3 -OH)16 ] 18+ with two ClO4 − as anion templates. The remaining Y 3+ ions were connected to the opposite position of (ClO4 )2 @[Y12 ( μ 3 -OH)16 ] 18+ through four l -L −, respectively. High-resolution electrospray ionization mass spectrometry (HRESI-MS) captured the signals of the cluster fragment Y12 (OH)16− x (O) x ( x = 4, 5, 6, 7, 8) and the unbroken dimer of Y12 (l -L)12 (OH)16− x (O) x 2 ( x = 4, 5, 12) from l -Y 14 in a mixed solution of methanol and dichloromethane, suggesting that Ln12 (OH)16− x (O) x is a stable cluster unit that could be further assembled into higher-nuclearity lanthanide–oxo clusters in solution. The solid-state circular dichroism (CD) spectra of compounds l -Y 14 /d -Y 14 and l -Dy 14 /d -Dy 14 displayed mirror symmetry effects in the range of 220–250 nm. The study of magnetic properties showed that l -Dy 14 had a weak antiferromagnetic interaction and displayed SMM-like behavior in the absence of a dc field.